THE COST OF A TRANSFORMER AND THE IMPORTANCE OF ITS HEATING - Sorimsokov Uchkun Soatboy o’g’li ,Boliyev Alisher Mardiyevich, Suyarov Anvar Olim o’g’li; Nurullayev O.U. (Academia Science Repository, 2023)
The problem of transformer losses and their causes are studied and recommendations for their optimal values are given. Transformer heating and cooling methods are studied.